Prolonged survival after surgery for ileal adenocarcinoma with ovarian metastasis: A case report - Prasad Kandel, Bishnu; Shah, Bikash; Diki Bista, Kesang (Journal of Chitwan Medical College, 2026)
Adenocarcinoma of the ileum is a rare malignancy. The prognosis largely depends on the stage at diagnosis, and metastatic disease typically carries a poor outcome. We report a case of prolonged survival following resection of ileal adenocarcinoma with ovarian metastasis. A 22‑year‑old female presented with mild lower abdominal pain. Ultrasonography revealed a left complex adnexal cyst. During laparotomy, two distinct masses were identified in the distal ileum and the left ovary. Segmental ileal resection with mesentery and left salpingo‑oophorectomy were performed. Histopathology confirmed primary ileal adenocarcinoma with ovarian metastasis. One year later, a CT scan showed a mesenteric mass, which was excised; histopathology again revealed adenocarcinoma. The patient remains disease‑free six years after the initial surgery. This case highlights the potential for long‑term survival following curative resection, even in advanced stages of ileal adenocarcinoma.